Advancing Varicocele Management: A Comprehensive Study on the Efficacy and Outcomes of Endovascular Techniques in a Tertiary Health Care Setting - Adheeni Suresh; Bhaskar M.V; Aswath Govindaraju; Suresh Soman (Journal of Clinical Interventional Radiology ISVIR)
Objective The aim of the study is to report the clinical outcomes of embolization for symptomatic varicoceles.